Pulse Low-Frequency Electrostatic Field Application for Injuries of Knee Joint Capsular Ligament Apparatus in Children: a Prospective Randomized Comparative Study - Ekaterina L. Vakhova; Dmitry Y. Vybornov; Elena A. Turova; Natalya B. Korchazhkina; Ivan N. Isaev (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
INTRODUCTION. Rehabilitation of children with knee joint injuries is very relevant due to a high prevalence of such a localization ofinjuries leading to loss of limb function and often requiring surgical treatment and intensive rehabilitation.AIM. To establish scientifically the isolated use of low-frequency pulsed electrostatic field and in combination with roboticmechanotherapy in treatment of the knee joint capsular ligamentous apparatus injuries in children.MATERIAL AND METHODS. 60 children aged 13 to 18 years with damage to the capsular ligamentous apparatus of the knee jointwere included in the clinical study. The study group was represented by 30 children receiving a combined effect of the low-frequencypulsed electrostatic field and robotic mechanotherapy. A comparison group of 30 children was exposed to the low-frequency pulsedelectrostatic field. Medical rehabilitation was prescribed in the early post-immobilization period after arthroscopic operations. Todetermine the effectiveness of medical rehabilitation techniques, we used orthopedic status assessment, a subjacent determinationof the severity of pain syndrome according to the VAS, clinical assessment of motor deficit, laser Doppler flowmetry, ultrasoundexamination of knee joints, infrared thermography, and psychological testing using the Spielberg-Hanin scale.RESULTS AND DISCUSSION. A prospective open randomized comparative study revealed a more pronounced regression of painsyndrome, earlier restoration of the motions in the injured joint, and relief of posttraumatic synovitis signs when using two physicalfactors in children with damage to the capsule-ligament apparatus of the knee joint in combination. The clinical and functional resultsobtained are of great importance in injuries of the knee joint with the risk of contracture formation in the postoperative period.CONCLUSION. High therapeutic efficacy, good tolerability of procedures, and the absence of adverse reactions substantiate expediencyof the low frequency pulsed electrostatic field introduction in combination with robotic mechanotherapy for injuries of the capsularligamentous apparatus of the knee joint in children into the practice of children's medical and preventive medical organizations.